2015
DOI: 10.1002/crat.201500031
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth, characterization and Density functional theory computations of supramolecular N‐carbamothioyl acetamide

Abstract: Single crystals of N‐carbamothioylacetamide (NCTA) were grown by slow evaporation technique at constant temperature. The structure is elucidated by single crystal XRD analysis. The studies reveal that the molecule is associated with accommodating weak C–O···H, N–H···O, N–H···S, C–H···N, C···C and H···H stacking interactions which are responsible for the formation and strengthening of supramolecular assembly. Inter‐ and intramolecular hydrogen bonding interactions exhibit supramolecular architecture in the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…A search through the Cambridge Structural Database [ 28 , 29 ] gave only one match [ 30 ] and zero match when N -carbamothioylacetamide and N , N′ -thiocarbonyldiacetamide were used as the query words respectively. Both the co-crystal and the previously reported N -carbamothioylacetamide have the same space group of P -1 [ 30 ]. However, further literature search revealed that the crystal structure of the ring-substituted thiourea compounds are available [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A search through the Cambridge Structural Database [ 28 , 29 ] gave only one match [ 30 ] and zero match when N -carbamothioylacetamide and N , N′ -thiocarbonyldiacetamide were used as the query words respectively. Both the co-crystal and the previously reported N -carbamothioylacetamide have the same space group of P -1 [ 30 ]. However, further literature search revealed that the crystal structure of the ring-substituted thiourea compounds are available [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, further literature search revealed that the crystal structure of the ring-substituted thiourea compounds are available [ 31 , 32 ]. The structure reported in this reference (CDS refcode KECHIJ01 and deposition number 1009665) [ 30 ], was the only structure which shared very close identities with the titled co-crystal, asides from the others with ring structures and thiourea moieties, whose properties have been well documented [ 31 , 32 ]. It is worthy of note that the stabilization of the co-crystal was ensured by both intra- and inter-molecular –C=O···H interactions, just as were observed in previous similar studies [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirshfeld surface analysis technique is exploited for the calculation of intermolecular interactions. Hirshfeld surface of the receptors is portrayed in Figure 9 with respect to various properties such as di, de, dnorm, shape index and curvedness (Prasad and Meenakshisundaram, 2015a). dnorm surface highlighted two bright red spots indicating the presence of close contacts interms of hydrogen bonding, as well as O-H and H-O interactions (Prasad and Meenakshisundaram, 2015b).…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%